The value co-creation in the digital business models: the Xelexia case - Pencarelli, Tonino; Conti, Emanuela; Gabbianelli, Linda (Piccola Impresa / Small Business, 2019)
The purpose of the article is to describe how value co-creation occurs in digital business models through the analysis of a digital online consulting platform.To pursue the research objective, the literature on the Business Model concept was analyzed, refer-ring to the digital context, analyzing the key contents of the value proposition and the main ways of co-creating/capturing and delivering value.The case of the Xelexia online consulting platform was selected in order to analyze and understand how the processes generated and share value are featured using the business model canvas scheme integrated with insights on the processes of co-creation of value realized among suppliers and cus-tomers. The success of the digital platform is based on the originality and uniqueness of the value proposition that consists in the effective matching system of supply and demand of technical and engineering skills and in the co-creation of value for and with customers and stakeholders. The study describes the logic of co-creation of value in the digital business model under examination, using the interpretative keys proposed by the perspectives of Service Dominant Logic and Experience Logic.